Cartas para CASA: reflexões sobre os sentidos da escola para jovens em conflito com a lei - Pelvini, Rafael Felix (2024)
This research is based on an initiative developed by the "Juventudes" program at Sesc in São Paulo, in partnership with Fundação CASA: a letter exchange between incarcerated adolescents and three educators, including the author of this dissertation. The aim is to understand, through reading these letters and the author's experience in social education, what the narratives of these adolescents can reveal about curriculum, education, and socio-education. The material consists of 285 letters written by male adolescents serving a socio-educational internment measure in the Grande ABC region, in São Paulo, between 2020 and 2021, during the COVID-19 pandemic crisis. The methodology is a sensitive analysis of these letters, intertwined with the author's participatory experience. The research is qualitative, critical, and participatory, capturing emotions, perceptions, and interpretations of the studied context (Chizzotti, 1991). The analysis of this content (Bardin, 1977) addressed the following categories: identity